2008
DOI: 10.1111/j.1365-2044.2007.05400.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the HemoCue® near patient testing device to measure the concentration of haemoglobin in suction fluid at elective Caesarean section*

Abstract: SummaryWe have investigated the suitability of the HemoCue Ò photometer to measure the concentration of haemoglobin in suction fluid obtained at elective caesarean section in 30 women. Laboratory analysis was used as a gold standard against which values generated by the HemoCue were compared. We used the method of Bland and Altman to analyse the data. The bias and the limits of agreement were )0.013 and )0.39 to 0.36 mg.dl )1 respectively, indicating a good level of agreement. Mean (SD) total blood loss calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…Oxytocin infusions were used prophylactically at obstetric request in 45 women (75%), at a standardised dose of 10 IU in 125 mL every hour for the first 4 h. Urine output during the first 6 h and at 12 and 18 h, according to body weight, are shown in Table 1, for the whole group and according to whether oxytocin infusion was used. Median (95% CI) 24-h intravenous fluid input were 2.8 (1.8-4.3) L. Median (IQR [range]) times to first oral fluids and cessation of intravenous fluid were 3 (2-4 [2][3][4][5][6][7][8][9][10][11]) h and 6 (5-7 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]) h. Mean (±SD) haemoglobin concentrations on the day of surgery and the following day were 11.9 (±1.2) and 10.5 (±1.0) g/dL, respectively. The mean (±SD) drop in haemoglobin concentration with or without oxytocin infusion was 1.4 (±0.9) and 1.4 (±0.4) mg/dL respectively; no patient received blood products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin infusions were used prophylactically at obstetric request in 45 women (75%), at a standardised dose of 10 IU in 125 mL every hour for the first 4 h. Urine output during the first 6 h and at 12 and 18 h, according to body weight, are shown in Table 1, for the whole group and according to whether oxytocin infusion was used. Median (95% CI) 24-h intravenous fluid input were 2.8 (1.8-4.3) L. Median (IQR [range]) times to first oral fluids and cessation of intravenous fluid were 3 (2-4 [2][3][4][5][6][7][8][9][10][11]) h and 6 (5-7 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]) h. Mean (±SD) haemoglobin concentrations on the day of surgery and the following day were 11.9 (±1.2) and 10.5 (±1.0) g/dL, respectively. The mean (±SD) drop in haemoglobin concentration with or without oxytocin infusion was 1.4 (±0.9) and 1.4 (±0.4) mg/dL respectively; no patient received blood products.…”
Section: Resultsmentioning
confidence: 99%
“…For this, we assessed the degree of dilution by amniotic fluid by measuring the haemoglobin concentration of the suction bottle using a HemocueÒ Hb 201 + Analyzer (Hemocue AB, Ä ngelholm, Sweden) and comparing it to the haemoglobin measurement from the full blood count on the morning of surgery measured on a Sysmex XE2100 machine (Sysmex UK, Wymbush, UK), a technique based on previous work. 10 An estimate of time to regression of neuraxial anaesthesia was made by return of full motor power to the lower limbs as assessed by the Bromage score with a score of 1 indicating no motor block. 11 A sample size of 60 was chosen to provide acceptable 95% confidence intervals, based on a variability seen in healthy individuals.…”
Section: Methodsmentioning
confidence: 99%
“…21,28 The haemoglobin content of the aspiration fluid can be used to estimate blood loss. 29 There is a high risk of underestimation during the postoperative period in the recovery room particularly in the absence of specific training of all relevant healthcare professionals, including nurses and anaesthetists.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospect it may have been preferable if we had defined this term. Unpublished data from a recent study in our unit, 25 revealed that there was an average perioperative drop in blood haemoglobin levels of 2.5 g/dL at elective caesarean section. With this in mind we could use a blood haemoglobin level of less than 10 g/dL for setting up the cell saver as a significant proportion of these patients would be expected to require a blood transfusion.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study in our unit when we were not using cell salvage showed that over 50% of blood lost at caesarean section is contained in the suction fluid. 25 It is very likely that if we also collected and processed the blood stained amniotic fluid we could significantly increase the amount of blood that we are able to recycle. There is some evidence to suggest that this is a safe strategy 19,26 and indeed there is no requirement that two suction devices should be used in the publication by NICE on cell salvage.…”
Section: Discussionmentioning
confidence: 99%